Effects of water-cement ratio and notches to the flexural strength of concrete - Mohamad Shazwan, Ahmad Shah; Norhazilan, Md. Noor; Beng, Ahmad Hong Kueh; Mohd. Nasir, Tamin (IOP Publishing Ltd, 2020)
It is often assumed that flexural strength of concrete has less significance impact on overall concrete strength. However, from fracture mechanics point-of-view tensile is an element the mechanics always look into due to cracking does associate with tension. In the research, fracture is translated into physical laboratory experiment by introducing notches. Physical laboratory works on concrete beams with three-point bend test configuration under static load and calculating outputs from laboratory with numerical equations. Three-point bend test method is conducted because from the testing, tensile strength or also recognised as flexural strength of concrete for each water-cement ratio could be attain. Thus, the aim of this article is to reveal and discuss the pattern of flexural strength of concrete on different water-cement ratio. The testing follows conventional fracture three-point bend test on concrete but with revised version by testing notched concrete beams. Normal three-point bend tests were run on concrete beams with different notch sizes; 30 mm, 15mm, and 5 mm respectively. There were three water-cement ratio decided in concrete mix; 0.3, 0.4, and 0.5. Thus, the trend of flexural strength of concrete follows the trend of water-cement ratio. Flexural strength increases when water-cement ratio increases up to water-cement ratio 0.5.